CRIMINAL LIABILITY FOR THE CORRUPTION OF MINORS: DOCTRINAL, PROCEDURAL, AND CRIMINOLOGICAL ASPECTS - Svitlychnyi , Oleksii (Collection of scientific papers «ΛΌГOΣ», 2025)
The issue of criminal liability for the corruption of minors belongs to an extremely sensitive and socially significant area of criminal law regulation. One of the key aspects of its understanding is the clarification of the elements of this crime, both from the standpoint of legal doctrine and through the lens of modern judicial practice. In particular, it is the correct understanding of the object, the objective side, the subject, and the subjective side that allows for clear differentiation of crimes under Article 156 of the Criminal Code of Ukraine from related sexual offenses, helps avoid law enforcement errors, and ensures an adequate level of protection of the victim’s rights.